2019
DOI: 10.1016/j.ijwd.2019.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of hidradenitis suppurativa: A review of the literature

Abstract: BackgroundHidradenitis suppurativa (HS) is a chronic inflammatory skin condition that affects the follicular portion of folliculopilosebaceous units. It causes painful nodules, abscesses, and draining sinus tracts throughout multiple regions of the body. HS primarily affects women; the overall HS prevalence in women is three times that in men. Although cutaneous disease itself causes substantial morbidity, recent evidence has shown that HS is a systemic inflammatory disease with multiple associated comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
1
28
0
2
Order By: Relevance
“…Interestingly, a Danish cross-sectional study showed that the mean heart rate in severe HS patients in resting conditions was suggestively higher when compared with that of controls [ 17 ]. Both HS and atherosclerosis have a chronic inflammatory subset, and cardiovascular and metabolic diseases are the most common comorbidities found in HS [ 18 , 19 ]. Atherosclerosis, a chronic inflammatory disease affecting the blood vessels, is considered a major cause of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a Danish cross-sectional study showed that the mean heart rate in severe HS patients in resting conditions was suggestively higher when compared with that of controls [ 17 ]. Both HS and atherosclerosis have a chronic inflammatory subset, and cardiovascular and metabolic diseases are the most common comorbidities found in HS [ 18 , 19 ]. Atherosclerosis, a chronic inflammatory disease affecting the blood vessels, is considered a major cause of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with psoriasis and hidradenitis suppurativa have increased the prevalence of cardiovascular risk factors, myocardial infarction, and mortality. [1][2][3][4][5][6] In addition, patients with psoriasis, acne, hidradenitis suppurativa, and alopecia areata are at an increased risk of mental health comorbidities, such as anxiety, depression, and suicidality. [7][8][9][10] While management of these comorbidities is often done by primary care providers, for some patients, their dermatologist may be their only point of contact with the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of HS varies from 0.05% to 4.1% 2 and it's more commonly seen in females 3 . HS has a significant burden of comorbidities beyond the skin, including metabolic, cardiovascular, endocrine, gastrointestinal, rheumatologic, and psychiatric disorders, which all decrease the quality of life 4 …”
Section: Introductionmentioning
confidence: 99%